KERAGAMAN SERANGGA PENYERBUK PADA PERTANAMAN STRAWBERY YANG DISELINGI DENGAN TANAMAN Borreria laevicaulis - Maryam Muji Lestari; Imam Widhiono; Eming Sudiana (Scripta Biologica, 2014)
The productivity of strawberry (Fragaria sp.) depends on the presence of pollinator insects that need nectar or pollen as their food. The diversity and the population size of pollinator insects can be increased by the companion planting of Borreria laevicaulis among the strawberry. This research aimed to determine the diversity of pollinator insects of strawberry plantation companion by B. laevicaulis and to determine the relationship between the diversity of pollinator insects with the strawberry fruit produced. This research was conducted in the strawberry plantation of Serang Village, of the District Karangreja, Purbalingga, from June to August 2012. The research was designed to determine the effect of companion planting of B. laevicaulis at the 0%, 5%, 10%, and 15% of the total individuals of strawberry. The results showed that the companion planting of B. laevicaulis in the strawberry field did not affect the species diversity of pollinator insects. But the B. laevicaulis companion planting affected the amount of strawberry yielded. The maximum yield was obtained by planting B. laevicaulis at the 10% of the strawberry individuals; it was increased by 76.12% of the control without companion planting.